The Effect of Economic Growth, Population, Minimum Wage, and HDI on Poverty (Efficient: Indonesian Journal of Development Economics, 2023)
The purpose of this study was to analyze the effect of economic growth, population, minimum wage, and human development index on poverty rates in Central Java Province. This study uses quantitative methods with panel data, which is a combination of cross-section data from 35 districts/cities in the Central Java Province and time series data for the period 2015-2019. Tests in did study with the Fixed Effect Regression analysis method with the Generalized Least Square (GLS). The results showed that the variable of economic growth and human development index had a negative and significant effect, the population variable had a positive and significant effect, and while poverty rate variable had a positive and not significant effect. Suggestions from the results of this study are: (1) The Local Government should try to push the equal whole infrastructure. (2) KB (Family Plan) Program should be focused in every area of villages. (3) Every regency needs to set the value of minimum paid based on worth life’s standard. (4) Increase the level of education in every village by repairing and adding more devices that support making education better.